THE EXPERIENCE OF HEXICON APPLICATION IN PREGNANT WOMEN WITH BACTERIAL VAGINOSIS IN ORDER TO PREVENT INTRAUTERINE FETAL INFECTION - Kaminskiy, V.V.; Eshchenko, E.G.; Zelenskaya, M.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The article contains  information about a problem of bacterial vaginosis development during pregnancy and its negative influence on current of gestation, labor and newborn condition . The circuit of treatment of bacteril vaginosis with Hexicon application is offered and the efficiency of its application is shown in pregnant women.